The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1158/1078-0432.ccr-13-1077
|View full text |Cite
|
Sign up to set email alerts
|

Distinction between Asymptomatic Monoclonal B-cell Lymphocytosis with Cyclin D1 Overexpression and Mantle Cell Lymphoma: From Molecular Profiling to Flow Cytometry

Abstract: Purpose According to current diagnostic criteria, mantle cell lymphoma (MCL) encompasses the usual, aggressive variants and rare, nonnodal cases with monoclonal asymptomatic lymphocytosis, cyclin D1–positive (MALD1). We aimed to understand the biology behind this clinical heterogeneity and to identify markers for adequate identification of MALD1 cases. Experimental Design We compared 17 typical MCL cases with a homogeneous group of 13 untreated MALD1 cases (median follow-up, 71 months). We conducted gene exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 48 publications
(65 reference statements)
0
49
0
2
Order By: Relevance
“…SOX11-negative MCL usually present clinically with non-nodal leukemic disease whereas SOX11-positive tumors involve lymph nodes and have extensive extranodal infiltration. 4,5 The SOX11-dependent "angiogenic switch" discovered in this study may explain MCL clinical heterogeneity because the low angiogenic potential of SOX11-negative cells may impair their tissue infiltration and retain them in the bloodstream whereas SOX11-induced angiogenesis facilitates tissue infiltration and growth of the SOX11-expressing MCL cells.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…SOX11-negative MCL usually present clinically with non-nodal leukemic disease whereas SOX11-positive tumors involve lymph nodes and have extensive extranodal infiltration. 4,5 The SOX11-dependent "angiogenic switch" discovered in this study may explain MCL clinical heterogeneity because the low angiogenic potential of SOX11-negative cells may impair their tissue infiltration and retain them in the bloodstream whereas SOX11-induced angiogenesis facilitates tissue infiltration and growth of the SOX11-expressing MCL cells.…”
Section: Discussionmentioning
confidence: 91%
“…2 However, recent studies have identified a subset of MCL with indolent clinical behavior that tends to present with leukemic disease instead of extensive nodal infiltration and patients may not need chemotherapy for long periods. [3][4][5] Recently, molecular studies have identified SOX11 (SRY [sex determining region-Y]-box11), as one of the best characterized discriminatory genes between these 2 clinical subtypes of MCL tumors. 6 SOX11, together with SOX4 and SOX12, belongs to the subgroup C of the SOX gene family encoding for transcription factors which play a critical role in embryonic development and cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…38 The clinical course of these seven cases was indolent, as none of the patients required chemotherapy for at least 2 years, a behavior similar to that described in other SOX11-negative mantle cell lymphomas. [7][8][9][10] To expand the analysis of the terminal B-cell differentiation program in mantle cell lymphoma, we investigated the expression of cytoplasmic immunoglobulin light chains, IRF4/MUM1, BLIMP1, and XBP1. A restricted and intense cytoplasmic light chain was seen more commonly in SOX11-negative (58%) than in -positive (13%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] The potential implication of SOX11 in the aggressive behavior of mantle cell lymphoma was initially suggested when it was recognized as one of the genes highly expressed in tumors requiring treatment at diagnosis compared with cases with a very indolent clinical course. 7 The relationship between the absence of SOX11 expression and an indolent clinical behavior of these tumors has been confirmed in subsequent studies [8][9][10] but not in others. 11 However, most aggressive SOX11-negative mantle cell lymphoma carry also TP53 mutations and may, therefore, correspond to a transformed form of these tumors.…”
mentioning
confidence: 90%
“…These cells may still retain biologic characteristics of normal mantle cells because at least some cases of monoclonal B-cell lymphocytosis-like nonnodal MCL appear to have an "in situ" MCL pattern when gastrointestinal staging biopsies are performed. 8 Although our understanding of the biology of SOX11 in MCL is significantly advanced through this article, 1 questions still of course remain. Some controversy does exist regarding the prognostic relevance of SOX11 because some groups have reported SOX11 as a favorable factor, whereas others report it as an adverse factor.…”
mentioning
confidence: 96%